Comparative study of surgical wound closure with nylon interrupted sutures and running subcuticular vicryl rapide suture after open release of the carpal tunnel - Vasileios Tzimas; Christos Kotsias; Charilaos Galanis; Georgios Panagiotakopoulos; Dimitrios Tsiampas; Juanita Parnis; Konstantinos Tilkeridis; Aliki Fiska (SAGE Publishing, 2022)
Background Surgical decompression of the carpal tunnel is considered the method of choice for its treatment with satisfactory results documented. Various methods and suturing materials have been used for closure of the surgical wound. In the present study, we compared interrupted mattress closure by means of nylon suture to running subcuticular closure with vicryl rapide suture. As far as we know, there is no similar study in the literature. Methods A total of twenty patients were included in the study. Ten of them had their surgical wound closed with 3.0 nylon suture in an interrupted fashion and for the rest, a running subcuticular 3.0 vicryl rapide was used. All patients filled in a questionnaire about VAS perceived pain and a Quick DASH score sheet, preoperatively, at two and six weeks postoperatively. The cosmesis of the scar was assessed using the POSAS v2.0 system at two and six weeks after surgery and overall incidence of infections was noted as well. Results There was no statistically important difference between the two groups of patients in regards to postoperative VAS pain levels at two and six weeks. Likewise, no statistically significant difference was evident as far as Quick DASH score, POSAS score and infections were concerned. Conclusions Our results suggest that the use of running subcuticular vicryl rapide suture is an attractive alternative to interrupted nylon sutures for closure after open carpal tunnel decompression, lacking any significant drawbacks. Lay Summary Surgery for carpal tunnel decompression is considered the method of choice for its treatment with documented satisfactory results. Various methods and suturing materials have been used for closure of the surgical wound. In the present study, we compared the use of a non-absorbable suture, placed intermittently to an absorbable continuous intradermal suture. A total of twenty patients were included in the study. Half of them had their wound closed with the absorbable suture and the other half with the non-absorbable suture, as described above. All patients were evaluated as far as pain, scar characteristics, functional outcomes of the operated hand and incidence of infection, at two and six weeks after surgery. After analysis of the data, no significant differences were found between the two groups, suggesting that both of these techniques are equally safe and efficacious.